Location of fragments in Pilon fractures and choice of the way for their repositioning and holding - Pobel, Anatoliy; Trufanov, Ivan; Gatsak, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
Pilon fractures are isolated in a separate group, which unites some similar signs: these fractures result from an axial load and their location is epimetaphyseal, fracture planes passing through the articular area of the tibia. The choice of the method of reduction and fixing of fragments in such compound and multiform fractures should be based on detailed knowledge of their configuration, mechanical cooperation as well as on the prognostic assessment of residual deformities. The work is based on experience of treating 51 casualties with fractures of the distal epimetaphysis of crural bones at the age from 18 to 80 years. It is shown that in pilon fractures of 43 B type the reposition of fragments by traction is effective, when the free tibial fragment is located on the anterointernal or posterointernal part of the epimetaphysis. If the fragment is located on the external part of the epimetaphysis and combined with a fibial fracture, an attempt to reduce it by traction is more often ineffective. In pilon fractures of43 Ctype it is possible to isolate the main fragment, which includes the largest part of the articular surface. Traction reposition of fragments in such a type of fractures was achieved in one third of patients with a small value of displacement. It is advisable to use close traction reposition (by traction or with a device) as the first stage, thereby making it possible to reduce the main fragments and reveal those ones, which are to be reduced in an open way. The above thing makes it possible to operate selectively and with little traumatism.